Innovations from the climate-smart villages inspired adoption of the CSV concept by research and development programmes in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Following visits to the Mali and Burkina Faso CSVs, Sasakawa Africa Association (SAA) is partnering with CCAFS to establish two CSVs in West Africa (Nigeria and Mali) and two CSVs in East Africa (Uganda and Ethiopia) in 2018. SAA which to promote CSVs as mean to popularize resilience-building natural resource management and CSA technologies throughout sub-Saharan Africa, in order to strengthen the capacity of its partners towards ensuring food security and increasing income of vulnerable smallholder farmers.